ANTIMICROBIAL UTILIZATION PATTERN OF URINARY TRACT INFECTION IN TERTIARY CARE HOSPITAL - S GIDAMUDI, SUNIL; A JADHAV, SUJATA; C KHANWELKAR, CHITRA; M THORAT, VANDANA; R DESAI, ROHIT; G NAIK, HARISH (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To study and analyze the pattern of antimicrobial utilization in urinary tract infection (UTI). Methods: A descriptive retrospective study was conducted in tertiary care hospital for 6 months including both male and female patients of all age groups. Case sheets diagnosed with UTI based on ICD-10 disease coding were collected from medical records department. The demographic data and prescription pattern of each case sheet were evaluated in detail. Drug utilization pattern was compared among different age groups of patients. Results: A total of 108 patients were included in the study, out of which 44.4% were males, and 55.6% were females. Most of the patients were in 40-60 years age group (40.7%). UTI confirmed by culture in 59.26% patients; in which Escherichia coli was isolated in 35.9% patients followed by Klebsiella species (14.06%) and Pseudomonas aeruginosa (7.8%). Cephalosporins (70.37%) were most commonly used antibiotic followed by fluoroquinolones (38.89%), penicillins (29.63%), azithromycin (17.59%), and aminoglycosides (15.74%). Among the cephalosporins, third generation parenteral was most commonly used. In penicillins, amoxicillin + clavulanic acid combination was used in 9 patients. Amikacin was most commonly used aminoglycoside followed by gentamicin. Mean duration of treatment was 6.28Â±3.02 days. Conclusion: Third generation cephalosporins (ceftriaxone and cefixime) were used as first line drug in most of the cases irrespective of the causative organism. This group should be reserved for complicated UTIs. Keywords: Urinary tract infections, Escherichia coli, Cephalosporins, Fluoroquinolones.